Sustainability disclosure and firm value: The intervening role of financial performance - Baroroh, Hilmy; Usholikhah, Nisa’ul (Faculty of Economics, Universitas Islam Indonesia, 2026)
Purpose – This study examines the extent to which non-financial reporting affects firm value.Methodology – This study employs panel data regression analysis using Generalized Least Squares (GLS) and Sobel tests to examine the mediation relationship between variables. The sample consists of companies listed on the IDX Sharia Growth database from 2020 to 2023, with an effective constituent period of December 2023 to May 2024.Findings – The results show that sustainability reports have a negative and significant effect on financial performance, while risk management and intellectual capital have positive and significant effects on financial performance. Sustainability reports do not affect firm value, while risk management and intellectual capital have a negative and significant effect on firm value, while financial performance has a positive and significant effect on firm value. Financial performance negatively mediates the relationship between sustainability reports and firm value. Implications – This research can provide insights for academics and various stakeholders in their efforts to increase firm value, from a management, investment, policy, or social responsibility perspective. Academics can explore how these factors interact in other industries or countries as well as how changes in regulation or market conditions affect these relationships.Originality – This study fills this gap by exploring the factors that influence firm value in the IDX Sharia Growth. It also used additional intervening variables to provide more comprehensive results.